Automatic Generation of GUI Interfaces from VDM++ Specifications: VDM++ GUI Builder - Carlos A. L. Nunes (2011)
The Vienna Development Method is supported by several tools. These tools allow generating Java code from a VDM++ specification but do not generate a graphical user interface (GUI). This paper aims to describe a generic approach and tool to automatically generate a GUI in Java from a VDM++ specification. The generated GUI calls methods of the VDM++ specification, which allows testing the specification itself in order to increase confidence that it is an accurate description of the intended behaviour. This GUI may evolve to interact with the already supported generation code in Java (for the API) in order to obtain a complete application from a VDM++ specification based on a fully automatic code generation process.